Influência da temperatura de alimentação de biocombustíveis no desempenho de motor agrícola - Gralick, Jonas (2018)
A search for alternatives to reduce the use of diesel within the national energy unit has been studied in a gradual way with biodiesel inserts to diesel, in order to reduce greenhouse gases. This is the result of the implementation of Law 13.263 / 2016, which is a mandatory addition of biodiesel in diesel, which is 15% in 2019. Parameters such as viscosity change when biodiesel is added to diesel, where this factor direct influence on fuel atomization and limitation in an engine. Thus, this work sought the behavior of renewable biofuels in a 61 cv agricultural engine, operating with blends of diesel, biodiesel and ethanol, which was tested on pure diesel and the proportions of 8, 15 and 20% biodiesel diesel, with and without ethanol, heating at 45, 65 and 85 ° C. The mechanical performance of the engine was measured by a eddy current dynamometer, and as gas emission by means of a combustion analyzer. The performance tests were performed on five replicates, while the submissions were done at a single time for each treatment. Regarding the performance of the engine, the specific weight was B0E1 at 85 ° C, while for the hourly consensus the lowest value was for the B20 at 85 ° C. The maximum power values were at 45 ° C, and the mixtures with the temperature level increased to the temperature of B15 at 85 ° C, 65 ° C. Rising fuel temperature, reducing heat, fuel temperature, reducing fuel temperature, reducing fuel temperature and reducing fuel consumption